The media of secular music in the medieval and early modern period (1110-1650) - Borghetti, Vincenzo, 1968-; Hatzikiriakos, Alexandros Maria (New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2024)
"This book brings a new perspective to secular music sources from the Middle Ages and early modernity by viewing them as media communication tools, whose particular features shape the meaning of their contents. Ranging from the eleventh to seventeenth centuries, and across countries and genres, the chapters offer innovative insights into the historical relationship between music and its presentation in a wide variety of media. The lens of media enables contributors to expand music history beyond notated music manuscripts and instruments to include images, furniture, luxury items and other objects, and to address uniquely visual and material aspects of music sources in books and literature. Drawing together an international group of contributors, the volume pays close attention to the medial and material dimensions of musical sources, considering them as multifaceted objects that not only contain but also determine the nature of music they transmit. Transforming our understanding of musical media, this volume will be of interest to scholars of musicology, art history, and medieval and early modern cultures"--
Part I: The materiality of song. The Codex Buranus, or The first chansonnier / Davide Daolmi ; Parchment poesis in Guillaume de Machaut's "Prologue" / Anne Stone ; Imaginary chansonniers : song, desire, and materiality in Vitsentzos Kornaros' Erotokritos / Alexandros Maria Hatzikiriakos -- Part II: Songs, books, society. Verbal and visual paratexts : strategies in shaping music books in the trecento Florentine manuscript tradition / Michele Epifani, Francesca Manzari, and Antonio Calvia ; Formes of intimacy : miniaturisation and sociability in the fifteenth-century chansonnier / Jane Alden ; The materiality of musical knowledge in sixteenth-century textbooks : appropriation, personalisation, and self-representation / Inga Mai Groote ; The modern music edition as material histor(iograph)y / Vincenzo Borghetti -- Part III: Picturing sound, hearing images. Secular sounds in late medieval lives of saints and their pictorial representations / Klaus Pietschmann ; The sounds of Poliphilo and Polia / Massimo Privitera ; The domestic life of the Syrinx / Tim Shephard -- Part IV: Musical objects. Music, heraldry and material culture in the late Middle Ages : Ars Nova songs for Louis I of Anjou and Bertrand du Guesclin / Yolanda Plumley ; Negotiating identity and status : musicalia in the relational strategies of Duke Guidubaldo II della Rovere / Franco Piperno ; Sacred music books desacralised : material perspectives on musical fragments / Matteo Nanni.
Keywords: Music in art; Music in literature; Music -- Manuscripts -- Europe -- History; Music -- 500-1400 -- History and criticism; Music -- 15th century -- History and criticism; Music -- 16th century -- History and criticism; Music -- 17th century -- History and criticism; MUSIC / General; ART / History / Medieval; ART / History / Renaissance